Experimental Study on Dynamic Performance of Self-Compacting Lightweight Aggregate Concrete under Compression - Furong Li; Zhenpeng Yu; Yanli Hu (Advances in Civil Engineering)
In order to study the dynamic characteristics of the self-compacting lightweight aggregate concrete (SCLC) under uniaxial compression, 10 different strain rates (10−5–10−1/s) were set up to examine the uniaxial compressive dynamic performance of ordinary concrete, lightweight aggregate concrete, and SCLC, respectively. The failure modes and stress-strain curves of the samples under different loading conditions were obtained through experiment. The dynamic characteristics of the SCLC were analyzed by comparing the failure modes and testing data under different loading conditions. The following conclusions are drawn: the failure modes of the SCLC belong to destruction of shale ceramsite, which are similar to that of the lightweight aggregate concrete. The peak stress and elastic modulus of the self-compacting lightweight aggregate gradually increase with the increase of the loading strain rate, but the extent of increase of the peak stress is lower than that of the ordinary concrete and lightweight aggregate concrete. Affected by the loading strain rate and the random coupling of concrete, the peak strain of the self-compacting lightweight aggregate shows a relatively discrete changing trend. At the same time, the compressive dynamic performance of the SCLC was analyzed from the perspective of failure mechanism with a quantitative point of view.